Study on Dynamic Responses of Unit Slab Track Considering the Influence of Cement Asphalt Mortar Rough Surface - Xianmai Chen; Yanping Pan; Xiangyun Deng; Nan Chen (Advances in Civil Engineering)
Due to the particularity of the construction technology of the CRTS I slab track bagging method, there is a certain roughness between the track slab and the mortar layer in the actual project. In this work, the W–M fractal function was used to simulate the cement asphalt mortar layer in unit slab track with roughness rough surface morphology. To investigate the effects of interlayer rough contact surfaces, an interactive modeling approach using Python–Abaqus was developed, namely, the track structure performance, interlayer contact behavior, and vertical dynamic responses. The fastener pivot point reaction of the vehicle–track coupled model interacts with the track structure to examine the impact of different fractal dimensions and scale coefficients under the dynamic train load. The numerical results demonstrate that as the fractal dimension D and characteristic scale factor G increase, the dynamic response of the track slab gradually increases, and the contact area between layers decreases. The stress of rough contact surface is pointing distribution. Among the components of the track structure, the displacement of the track slab is most affected by the roughness. The rough surface affects the fatigue life of the mortar and consequently affects the service performance of the track structure. This study explores the effect of rough surfaces on the performance of CRTS I slab track structures under dynamic train load and provides a reference for improving the design of track structures and enhancing its life.